EDUKASI KESADARAN PAJAK BAGI MAHASISWA SEBAGAI WARGA NEGARA MELALUI ROLE PLAYING - Listyowati, Maria Yosepin Endah; Achwan, Muhammad; Suyani, Suyani; Prihatin, Lilik; Bilyastuti, Mai Puspadyna; Muharijanto, Rijono Eko; Widodo, Fajar Bayu; Firmansyah, Mahardika Danam Yusuf; Sarengat, Sarengat (Universitas Mataram, 2025)
Tax is a mandatory contribution that must be paid to the state by every individual or entity and is mandatory based on the Law, without any direct compensation, to be used to finance various state interests for the greatest prosperity of the people. Therefore, knowledge and understanding of the objectives and benefits of taxes are very important for all levels of society, including students as the next generation of the nation who will determine the direction of the country's development in the future. This community service activity aims to provide tax education not only through theory but with a project-based learning approach that uses problem-solving-based role-playing techniques which are one form of learning in higher education. The implementation of this activity involved 51 participants in the second semester who took the general basic course of Citizenship Education II from various study programs, namely Law, Management, and Public Administration at PSDKU Ponorogo, Merdeka University of Malang who actively participated. In the implementation of tax awareness learning in higher education with group discussion and role-playing methods is one of the effective strategies to instill the values of legal awareness from an early age. Through group discussions, students are trained to think critically, express opinions, and understand various points of view regarding tax obligations. Meanwhile, the role-playing model provides real-life experiences that encourage students to be active, responsible, and understand their respective roles in the tax system. Therefore, the combination of these two methods helps shape students' character, making them legally aware, disciplined, and socially responsible as citizens. The integration of tax materials and problem-solving-based Civics Education serves as a socialization tool that encourages students to comply with taxes to strengthen the national economy.